Automatic generation control of restructured power systems with combined intelligent techniques. (11th March 2010) - Sinha, S.K.; Prasad, R.; Patel, R.N.
In this paper different artificial intelligence techniques have been used for the automatic generation control of two area restructured power system for bilateral contracts. Bio-inspired computation techniques such as genetic algorithm and particle swarm optimisation have been used to optimise the parameters of a fuzzy based controller for a two area power system. An attempt has been made to compare the performances in terms of time taken to damp out oscillations in the two areas. Other parameters for comparison include the final steady state value of frequency, tie-line power interchange and power generated by different generating companies (GENCOs) in the event of load change for different controllers in automatic generation control (AGC) system. The concept of distribution companies (DISCO) participation matrix to simulate bilateral contracts is used in this study.